Ant (Hymenoptera: Formicidae) diversity influenced by tree thinning in the Western Australian jarrah (Eucalyptus marginata) forest - Heterick, Brian E.; Majer, Jonathan; Kabay, E.; Loh, M. (Royal Society of Western Australia Inc., 2015)
The Western Australian Water Corporation has trialled a catchment – management program in the northern jarrah forest as a possible means of enhancing water runoff and yield. Thinning has been performed by chemical injection of trees and/or by logging. This paper reports on the impact of this program on a prominent indicator component of the biota, the ant fauna. Six plots were sampled in 2006, prior to treatment and afterwards in 2008 and 2009. Two plots were unthinned controls, two were thinned, one was thinned and logged and the other was thinned, logged and burned, resulting in representations of a gradient of intervention. However, ant abundance increased in all treated plots, especially so in the thinned, logged and burned plot. Over the three years, species richness increased in Control Plot 2, in thinned by stem injection Plot 3, in thinned by logging and burned Plot 5 and in thinned by logging Plot 6 but declined in thinned by stem injection Plot 4 and recovered somewhat but did not attain 2006 levels in Control Plot 1. Ant species evenness declined in the two thinned by logging plots. An NMDS ordination indicated that the degree of change in ant assemblage composition was lowest in the controls, increased in the thinned plots and by a further increment in the thinned by stem injection and thinned by logging plot, and was greatest in the plot that had been burned. In summary, the various shifts in ant dynamics do not present a clear pattern over all the plots. The most noticeable changes were a shift in equilibrium between ant ecological groupings noticed in plot 3 in 2008 and the loss of cover-loving species in Plot 5 and their replacement by those that favour open ground. Plot 5, where burning was conducted, produced results that suggest an ant fauna adapted to cool, moist conditions may be in the process of being replaced by one favouring warmer conditions; with under cover nesters also replaced by open soil nesters. Potentially, there could be a loss of some species with depauperisation of the ant fauna overall. At the same time, there were no signs that the environment was being so seriously degraded that native dominants such as Iridomyrmex chasei Forel and meat ants or exotics like Pheidole megacephala (Fabricius) or the Argentine ant (Linepithema humile (Mayr)) were establishing colonies. Such species appeared to be completely absent from the survey sites.